1971
DOI: 10.1002/kin.550030203
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of theory and experiment in the ethane–methyl radical system

Abstract: A critical examination has been made of some aspects of the thermal decomposition of ethane and the reverse recombination reaction. The experimental Arrhenius A-factors for ethane are, in general, smaller than those which are calculated from thermodynamic quantities together with the observed rate constants for methyl recombination. Theoretical calculations also illustrate a discrepancy between the experimental work on recombination and decomposition. The experimental shapes of k/k, falloff curves and the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

1972
1972
1977
1977

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 56 publications
2
23
1
Order By: Relevance
“…Experimental values are extremely scattered [4] but are more concentrated at the lower end of these ranges, and in some instances are lower than any of the above theoretical values: at 873"K, Trenwith obtained Pl/z = 6.3 torr [31b]. Our calculated Pl,z values (Table 111) are lower than any of the above, except that of Trenwith.…”
Section: Thermal Unzmolecular Fall-off Calculationscontrasting
confidence: 42%
“…Experimental values are extremely scattered [4] but are more concentrated at the lower end of these ranges, and in some instances are lower than any of the above theoretical values: at 873"K, Trenwith obtained Pl/z = 6.3 torr [31b]. Our calculated Pl,z values (Table 111) are lower than any of the above, except that of Trenwith.…”
Section: Thermal Unzmolecular Fall-off Calculationscontrasting
confidence: 42%
“…In recent years there has been growing evidence that Arrhenius plots for some simple hydrogen abstraction reactions show marked upward curvature in the region 700-1500 K so that rate constants measured at these temperatures are considerably higher than predicted from the simple Arrhenius equation measured at lower temperatures. This behaviour has been discussed by Clark and Dove (6) who have shown that the observed increase in activation energy for reactions such as [2] and [4] may be accounted for within the framework of transition-state theory. The present results provide confirmation of this behaviour for the reaction of methyl radicals with ethane.…”
Section: Reaction Of' Methyl Radicals With Ethanementioning
confidence: 71%
“…were measured relative to the rate constant for the reaction of methyl radicals with deuterium. If the temperature-dependence of the activation energy for the latter reaction was about the s a m e as that for reaction 4 appears to be (6), then their ratio would show no upward curvature in the Arrhenius plot, and the low values reported for k4 are explained.…”
Section: Reaction Of' Methyl Radicals With Ethanementioning
confidence: 96%
“…After several trials, we have found that the best correlation can be made with a model generally similar to Rabinovitch and Setser's [ 141 complex 2, Lin and Laidler's [ 151 model IV, and Waage and Rabinovitch's [16] model. In all of these models, the torsional vibration of ethane is assumed to become a free rotor in the complex, while four of the molecular bending vibrations take on substantially lower frequencies in the complex.…”
Section: Resultsmentioning
confidence: 94%